Modified Multivisceral Transplantation with Native Spleen Removal in Rats - Stringa, Pablo; Arreola, Nidia Monserrat; Moreno, Ane M. Andres; Largo, Carlota; Rumbo, Martín; Hernandez, Francisco (European Journal of Pediatric Surgery, 2019)
Background Modified multivisceral transplantation (MMVTx) refers to the use of a graft that includes all abdominal organs except the liver. The use of this type of transplant in children and adults expanded over the last years with good results. However, long-term survival in experimental models has not been reported. Our aim is to describe in detail some technical modifications of MMVTx to obtain long-term survival.Materials and Methods Syngeneic (Lewis–Lewis) heterotopic MMVTx was performed in 16 male rats (180–250 g). All procedures were performed under isoflurane anesthesia. The graft consisted of stomach, duodenopancreatic axis, spleen, and small bowel. The vascular pedicle consisted of a conduit of aorta, including the celiac trunk and the superior mesenteric artery (SMA), and the portal vein (PV). The engraftment was performed by end-to-side anastomosis to the infra-renal cava vein and aorta. After reperfusion, the graft was accommodated in the right side of the abdomen, and a terminal ileostomy performed. The native spleen was removed.Results Donor and recipient time was 39 ± 4.4 minutes and 69 ± 7 minutes, respectively; venous and arterial anastomosis time was 14 ± 1 minutes and 12.3 ± 1 minutes, respectively. Total ischemia time was 77.2 ± 7.9 minutes. Survival was 75% (12/16), six were sacrificed after 2 hours, and six were kept alive for long-term evaluation (more than 1 week).Conclusion Long-term survival is reported after heterotopic MMVTx in rats. The heterotopic MMVTx with native spleen removal would potentially improve the existent models for transplant research. The usefulness of this model warrants further confirmation in allogeneic experiments.
Keywords: modified multivisceral transplantation; multivisceral transplantation; rats; spleen; intestinal transplantation